Giant negative photoconductivity in La0.7Ca 0.3MnO3 thin films [Articol] - Moșneaga, Vasilii; Giske, Arnold; Samwer, Konrad; Mișina, Elena; Tamura, Takehisa; Nakabayashi, Seiichiro; Belenciuc, Alexandr; Șapoval, Oleg; Culiuc, Leonid (My University, 2004)
The increase of the resistance up to two orders of magnitude under laser illumination (l5760 nm) was observed in La0.7Ca0.3MnO3 ~LCMO! epitaxial thin films in ferromagnetic state.Optical absorption also increases by 10–15 % and the magnetic second-harmonic generation signal decreases down to zero under the irradiation. The light induced changes are reversible with decreases down to zero under the irradiation. The light induced changes are reversible with characteristic relaxation times t;1 – 30 s. Magnetic field, B54 T, suppresses the photoconductivity and decreases its relaxation time. Photoinduced effects are caused by the injection of a large number of extra carriers, which change the ~antiferromagnetic! AFM/FM phase balance in LCMO, favoring the insulating AFM state.